A National Cross-Sectional Survey on Work Environment Associated With Psychological Well-Being and Job Satisfaction Among Chinese Employees. (May 2020) - Zeng, Zhi; Liu, Jun; Xie, Qiong; Wu, Yali; Wang, Hua; Lu, Liming
Work environments can affect job satisfaction and psychological well-being. Using the job demand-control model as a foundation, this study aimed to explore the relationships between physical and psychosocial work environments and psychological well-being and job satisfaction in the workplace. A multistage sampling method was used with the 2012 China Labor-force Dynamics Survey among 4442 employees. Our outcome measures included psychological well-being and job satisfaction. The final model showed migrants (odds ratio [OR] = 1.34, 95% confidence interval [CI] = 1.13-1.60) and nonmanagerial employees (OR = 1.49, 95% CI = 1.25-1.78) who worked in general enterprises (OR= 1.61, 95% CI = 1.34-1.92) or suffered longer weekly work hours (OR = 1.42, 95% CI = 1.24-1.63) had worse psychological well-being or lower job satisfaction. Following the job demand-control model, higher job demands and lower job autonomy were significantly and positively associated with worse psychological well-being and lower job satisfaction. This study highlights that improved work environments can protect employees' well-being. Policymakers must provide better work environments. They must consider its physical environment (stable work contract and short work hours) and psychosocial environment (low job demands and high job autonomy) aspects, particularly for migrants and nonmanagerial employees.